Pengembangan Modul Ajar IPAS Berbasis Kurikulum Merdeka Dalam Upaya Peningkatan Hasil Belajar Siswa Kelas IV SDN Sukabumi 2 - Ismi Arofah; Ninik Indawati; Onik Ni’matul Farida (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
This research used the 4D development stages proposed by Thiagarajan (1974). This research aims to (1) determine the steps for preparing the Class IV Science Teaching Module Based on the Merdeka Curriculum My Indonesia Rich in Culture Material, (2) analyze and determine the level of appropriateness of the IPAS teaching module being developed, and (3) analyze the level of practicality of the Class IV IPAS teaching module. The resulting development product is a class IV science and science teaching module based on the Independent Curriculum. To determine the acceptability of the product, an expert validation test was carried out in terms of content, language, and presentation of the Class IV Science Teaching Module material and My Indonesia is Rich in Culture, and a validation test of the practicality of using the teaching module (teacher). This research instrument is in the form of questionnaires, observations, and interviews used to determine product acceptability. The assessment results were analyzed using descriptive analysis techniques. The research results obtained from the validation results of expert and user tests (class IV teachers and students) show that the Class IV IPAS teaching module meets the acceptability criteria for content, language, presentation, and practicality appropriateness. The scores obtained from the results of validation of expert tests on content aspects (76.04%), validation of language aspects (85%), validation of presentation aspects (93.75%), and user tests (81.25%) fall into the excellent category sound and no need for revision. Thus, the class IV science teaching module with the material My Indonesia is Rich in Culture can be used in science learning in class to improve student learning outcomes.